"Technophilia": A new risk factor for electronic cigarette use among early adolescents?. (April 2019) - Barrientos-Gutierrez, Inti; Lozano, Paula; Arillo-Santillan, Edna; Morello, Paola; Mejia, Raul; Thrasher, James F.
Abstract: Purpose: Develop and validate a scale that measures Technophilia (positive orientation toward new technology) and use it to address orientation toward new technologies to explain e-cigarette trial and adoption, especially in relatively low risk adolescents. Methods: Survey data were obtained from students of the three largest cities in Mexico ( n = 8123). We developed eight questions involving access, use and pleasure from different electronic media to measure technophilia. Exploratory factor analysis (EFA) was conducted. Linear GEE models were used when regressing technophilia on covariates. When regressing e-cigarette and conventional cigarette trial and use, logistic GEE models were used. Finally, we used multinomial logistic regression to evaluate the associations between technophilia and e-cigarettes as the first tobacco product. Results: Technophilia were correlated with theoretically-related variables. Unadjusted and adjusted models regressing e-cigarette trial and use indicated that students in the highest quartile for technophilia were more likely to have tried e-cigarettes compared with the lowest quartile (AORQ4 vs Q1 = 1.36, 95% CI 1.14–1.62). Technophilia was not independently associated with current e-cigarette use in adjusted models. Students with higher technophilia were more likely to have first tried e-cigarettes in both crude and adjusted models (AORQ4vQ1 = 1.66, 95% CI 1.20–2.31; AORQ3vQ1 = 1.43, 95% CI 1.02–2.01). Technophilia did not have a statistically significant, independent association with first use of other tobacco products. Conclusion: This study suggests that technophilia is associated with trial of e-cigarettes among youth. The measure we developed appears useful for understanding why some youth are open to trying novel, technologically oriented ways to consume nicotine.